Prevalence, Characteristics, and Epidemiology of Microbial Hand Contamination Among Minnesota State Fair Attendees (2014) - Mason, Meghan R.; Morawski, Bozena M.; Bayliss, Ruby L.; Noor, Fatuma M.; Jama, Sagal H.; Clabots, Connie L.; Johnson, James R. (Frontiers in Public Health, 2020)
Background: Many antimicrobial-resistant infections are community-acquired, yet community carriage of microorganisms by healthy individuals is poorly characterized. We assessed microorganism carriage on the hands of Minnesota State Fair attendees and explored associated factors. Methods: Minnesota State Fair attendees (in 2014) from households with ≥ 2 members (≥ 1 member being < 19 years old [a child]) were eligible to participate. Participants provided biological samples via a hand plating technique and completed a questionnaire on factors potentially related to microorganism carriage. Using presumptive taxonomic identifications and disk-diffusion-determined resistance phenotypes, hand-culture isolates were classified by microbial type; types were grouped into four broad categories based on inferred pathogenicity and consistency with the skin microbiota. Descriptive statistics, Χ2 tests, and generalized linear mixed-effects models were used to explore associations between survey and culture data. Results: We enrolled 206 participants from 82 households during 2 days; 50% of subjects were children. Overall, 99.5% (205/206) of hand samples yielded microorganisms. Most were non-pathogenic, whether skin microbiota (98.5% of participants) or non-skin microbiota (93.2% of participants). Only 2.4% (5/206) of samples yielded antibiotic-resistant bacteria. Children were more likely than adults to carry potentially pathogenic (OR = 3.63, 95% CI: 1.66-7.93) and presumably non-pathogenic (OR = 6.61, 95% CI: 1.67-26.15) non-skin microorganisms. Conclusions: Large community gatherings can serve as efficient sites for estimating the prevalence of microorganism carriage. A small proportion of participants carried antimicrobial-resistant pathogens on their hands; most carried non-pathogenic microorganisms, and no exposures specific to the state fair were associated with microorganism carriage.